Managing unwarranted variation in hospital care - findings from a regional audit in Norway - H. P. Eide; P. Barach; E. Søreide; C. Thoresen; O. Tjomsland (Springer, 2023)
Abstract Background/Aim There has been increasing focus and research over the past decades on defining, identifying, visualizing and reducing unwarranted clinical variation in clinical practice. Both clinician-driven initiatives such as the US based "Choosing Wisely" campaign and the top-down driven "Evidence-based intervention programme (EBI)" launched by NHS UK to improve quality of care by reducing unnecessary interventions have shown marginal results. We present the findings from a mixed-methods audit performed to evaluate the compliance by senior hospital leaders of a new regional strategy to reduce unwarranted variation in outcomes and utilization rates. Methods Seventy-five mid- to senior-division and department leaders from eight hospital trusts in South-Eastern Norway Regional Trust (HSO) were invited to participate in evaluating the response and compliance of the regional leadership strategy for reducing unwarranted variation in patient outcomes and service utilization rates. Results The audit revealed that the aim of reducing unwanted variation was not clearly communicated by senior HSO management. There was varying use of data from the national quality registers and health atlases for quality improvement. One third of the clinical leaders reported a lack of scrutiny of their work and were insufficiently aware of the HSO's top-management and the hospital's Boards strategic expectations about the importance of reducing unwarranted variation in their hospital utilization. Conclusions We found that the strategic aim of reducing unwanted clinical variation was not clearly communicated by senior HSO management to hospital boards and senior management. The hospitals could benefit from a better understanding of causes of variation by strengthening their efforts to reduce unwarranted variation in utilization rates as a key element in improving health care quality and patient safety. The findings of the audit are relevant for other healthcare organizations trying to improve their quality and reduce unnecessary variation.